(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
There is a large area of abandoned land that is not taken manage of after plantation activities in the tropic. These abandoned gardens which have been neglected for a long time have important ecological and economic values. This study aims to assess the existence of abandoned land in the tropic from an ecological and economic perspective. The ecological aspects assessed were stand structure, floristic composition, and species diversity. Meanwhile, the economic aspects analyzed were log price, harvesting cost, profit margin, and stumpage value. The vegetation survey was carried out on all woody trees with a diameter at bresst height (DBH) > 5 cm in 10 subplots each sized 20 m × 20 m. A total of.192 trees were recorded of 29 species belonging to 19 genera and 17 families. The most dominant species were Macaranga triloba (Importance Value, IV of 46.16), Macaranga tanarius (IV of 22.97), and Nephelium lappaceum (IV of 20.94). The indexes of diversity, dominance, evenness, and richness in the studied plots were 1.33, 0.06, 0.40, and 5.33, respectively. The means of wood price, logging cost, profit margin, and stumpage value at abandoned land were USD199.55 m-3, USD69.01 m-3, USD25.45 m-3, and USD51.56 ha-1, respectively. The abandoned lands with high ecological and economic value indicate the important role of abandoned lands in the secondary succession process in the tropics.